Analysis of Pork Marketing in the Market Traditional Karo Regency - Tarigan, E. I.; Daulay, H. A.; Hasan, F.; Sukarpi (Jurnal Peternakan Integratif, 2021)
Meat is one of animal protein sources and is widely consumed by the community, especially in the Karo Regency area. This research aims to identify the characteristics of marketing agencies, marketing channels, marketing margin, farmer share, and pork marketing efficiency in the traditional market of Karo Regency. The method used in data collection is the withdrawal of samples of dilution traders using purposive sampling methods, while samples of breeders and other marketing agencies by tracing methods, data collection is done by interview techniques using questionnaires. Data analysis includes marketing costs, marketing margins, and farmer shares of each marketing channel. The results of this study show that there are two marketing channels namely level I marketing channels consisting of merchants and breeders while level II marketing channels consist of breeders, agents, and retailers. The smallest marketing margin is obtained by the first marketing channel. The largest farmer share was acquired by the first channel. This channel only uses retailer merchants as intermediaries. In this study, both marketing channels are already efficient.